2015
DOI: 10.3390/nu7095355
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Patterns Are Associated with Elevated Blood Pressure among Qatari Women of Reproductive Age: A Cross-Sectional National Study

Abstract: Women of childbearing age are particularly vulnerable to the adverse effects of elevated blood pressure (BP), with dietary and lifestyle habits being increasingly recognized as important modifiable environmental risk factors for this condition. Using data from the National STEPwise survey conducted in Qatar in year 2012, we aimed to examine lifestyle patterns and their association with elevated BP among Qatari women of childbearing age (18–45 years). Socio-demographic, lifestyle, dietary, anthropometric and BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 73 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…TV/computer use and/or screen time was the most common proxy measure for sedentary behaviour (32); only six studies reported total sitting time. Some studies used reliable and validated instruments like the IPAQ/IPAQ-short (physical activity-12 studies; sedentary behaviour-5 studies [ 41 , 49 , 56 , 67 , 68 ]), GPAQ (physical activity-11 studies, sedentary behaviour-4 studies [ 16 , 54 , 69 , 70 ]) and the ATLS (physical activity-16 studies, sedentary behaviour-15 studies). Many studies developed their own tools (29 studies examining physical activity and 8 studying sedentary behaviour), eleven provided very limited description of the tools in terms of measuring frequency, intensity and duration of physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TV/computer use and/or screen time was the most common proxy measure for sedentary behaviour (32); only six studies reported total sitting time. Some studies used reliable and validated instruments like the IPAQ/IPAQ-short (physical activity-12 studies; sedentary behaviour-5 studies [ 41 , 49 , 56 , 67 , 68 ]), GPAQ (physical activity-11 studies, sedentary behaviour-4 studies [ 16 , 54 , 69 , 70 ]) and the ATLS (physical activity-16 studies, sedentary behaviour-15 studies). Many studies developed their own tools (29 studies examining physical activity and 8 studying sedentary behaviour), eleven provided very limited description of the tools in terms of measuring frequency, intensity and duration of physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 27 studies reporting on the prevalence of physical activity (Table 3 ), 11 were on the adult population in four countries: Oman, Qatar, Saudi Arabia and the United Arab Emirates. Four were population-based with three gathering data nationally through household interviews [ 39 , 54 , 69 ] and one by telephone in one city [ 76 ]. Two studies were conducted in Saudi Arabia with large differences in the prevalence of physical activity; for a national study the prevalence was very low (Men: 6.1 %, Women: 1.9 %) [ 39 ] while in the telephone-based study in Riyadh reported that more than half were met physical activity recommendations (Men: 56.3 %; Women: 65.7 %) [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lifestyle pattern consisting of a higher snack and dairy consumption and lower levels of physical activity was associated with obesity and unfavorable glycaemic indices, lipid profile and increased high-sensitivity C-reactive protein concentrations among urban Sri Lankan women [ 4 ]. In addition, a previous study by our group investigating the role of combined lifestyle factors on elevated blood pressure showed that a higher adherence to the ‘Fast food and smoking’ and the ‘Traditional and sedentary’ patterns increased its odds among Qatari women [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when a large number of variables are entered in a regression model, it is possible to obtain significant association simply by chance [ 3 ]. Recently, a novel approach in nutritional epidemiology has been proposed whereby lifestyle patterns, as a combination of diet, physical activity and smoking are examined in relation to diseases such as diabetes [ 4 ]; obesity [ 5 ] and hypertension [ 1 , 6 ]. Not only does this approach account for the collinearity between risk factors, it also captures the complexity of real lifestyle effect on disease risk and leads to a better understanding of high-risk behaviors.…”
Section: Introductionmentioning
confidence: 99%